Error Control Mechanisms and Data Recovery in Network Protocols - Huk, A. S.; Smal, Y. O.; Tiurin, A. P. (NURE, 2025)
The reliability of data transmission in computer networks critically depends on mechanisms of error control and data recovery. These mechanisms ensure that transmitted information remains accurate and consistent despite channel noise, packet loss, or network congestion. Modern protocols use a combination of error detection codes, error correction techniques, and retransmission strategies to maintain communication integrity. This paper provides an overview of fundamental and advanced methods applied in TCP/IP, wireless networks, and real-time applications, analyzing their role in achieving robust and efficient communication.
Keywords: error control; network protocols; data recovery; error detection; retransmission; reliability